Te Acercamos El Mundo Por Que Tus Sueños Viajan Con Nosotros. Estudio De Caso: Implementación De Una Agencia De Viajes Y Operadora De Turismo En La Ciudad De Riobamba Provincia De Chimborazo - Vásconez, Rita Sulema Lara; Quinchuela, Flor; Romero, Jenry Ernesto López (European Scientific Journal, ESJ, 2016)
The study of the facility permitted to determine that the implementation of the travel agency and the operator of tourism Sumak TourismRio in the city of Riobamba, in Chimborazo Province is possible or viable. Techiques of documentary and local investigations were used. In order to accomplish this investigation, a fundamental point of reference, the commercial viability of the project, was taken, which is based on the study of the market. This study was done considering the analysis of the demand. For this an instrument of investigation that in this case was the inquest guide was applied, which permitted the direct collection of information. On the other hand an analysis of the competition considering the local investigation was made considering the tourism organizations (travel agencies and operators of tourism) of the city of Riobamba which offer tourist products of similar characters. Furthermore the projection of the future demand and future competition, using the method of combined increment whose mathematatic method is: Cn=Co(1+i) . Also the unsatisfacatory existence, that is the confrontation of these factors considering un a difference. It is valid review the importance of the analysis of the demand, since it contributes to the definition of the description of the tourist. Considering all the information collected, the following was defined: the universe of the study shows different requirements in reference to tourist packets that the company offers, which permits economic benefits and by this means activate the economy of the city. Finally, it was shown that the sale of tourist packets Will permit the capitalization of the organization, producing a positive financial profit, since the investment produced will be recuperated in the first year of operation, producing an internal profit of 1,493%, an actual net amount of 2,625610.27(dollars) and a cost benefit of 104.19.